ACCELERATING THE GROWTH OF ONLINE EDUCATION PLATFORMS TO SPEED UP PROCEDURES (American Journal of Pedagogical and Educational Research, 2023)
The dramatic growth in digitalization made youth to be surrounded with technological advancements, hence they want these technologies being used in everywhere as they understand them well. However, older generation, who grew without these types of advancements have faced with problems in using digital tools to hold innovative classes. This, in turn, created some barriers between students and teachers, and encouraged institutes to work on implementing strategies to have balance on new innovative classes and traditional method of teaching. Therefore, the following research is going to outline how digital classes lead to benefits and what kinds of steps should be taken in order to implement tools to lectures as well as seminars for preventing any barriers that may damage to the process of teaching and learning in higher education system.